Experimental and analytical evaluation of bending for aluminum - Nazrith, Zulkafli (2012)
Spring-back is a common phenomenon that occurs in sheet metal bending after unloading the tooling or punch due to material elastic recovery. Three different thicknesses, 1, 2 and 3 mm are selected and 0o, 45o and 90o of orientation are chosen as the considered parameters while the 30o is selected as reference bending angle. In this research, it studies about determining the spring-back angle by using experimental and analytical method. Different equations are use where the Daw-Kwei Leu equation as the first equation is considers the thickness poisson ratio and strain hardening exponent while the Dongye Fei and Peter Hodgson equation is only consider the thickness effect, poisson ratio and die width for spring-back. Experiment for bending is limited in bottoming v-die bending. Data from the tensile test are used in determining the spring-back value for analytical method while press brake machine is a tool to complete the test. As the finding of the research, increasing the sheet thickness is decrease the spring-back value for analytical and experiment. In experiment, 1 mm and 2 mm gain a decreasing spring-back value related with analytical and previous study, but 3 mm of thickness has a spring-go appearance where the outer layer of outer diameter is happened a crack and this is proved the result where the material already exceed the elastic region for the aluminum.